2013
DOI: 10.1002/cmdc.201300286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Linker Length and Composition on Heterobivalent Ligand‐Mediated Receptor Cross‐Talk between the A1 Adenosine and β2 Adrenergic Receptors

Abstract: Heterobivalent ligands that possess pharmacophores designed to interact with both the A1 adenosine receptor (A1 AR) and the β2 adrenergic receptor (β2 AR) were prepared. More specifically, these ligands contain an adenosine moiety that is linked via its N(6) -position to the amino group of the saligenin-substituted ethanolamine moiety present in the well-known β2 AR agonist, salbutamol. The affinities of these ligands were determined at both receptors and found to vary with linker length and composition. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Indeed, the prevalence of heteromers within the adrenergic receptor systems makes them interesting targets for the treatment of various cardiovascular ailments. For example, Karellas et al introduced heterobivalent molecules targeting β2-adrenergic receptor/adenosine A 1 receptor (β 2 AR/A 1 AR) heteromers in an effort to understand the cross talk among these two cellular cAMP regulating receptors; it was proposed that careful balance between the signaling pathways generated by the two receptor monomers conforming this heteromer could aid in the prevention of certain cardiac arrhythmias . Due to the importance of functions regulated by this receptor system, it has become the focus of significant analysis via heterobivalent ligands …”
Section: Bivalent Molecules For Other Gpcrs To Study Homomers and Het...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the prevalence of heteromers within the adrenergic receptor systems makes them interesting targets for the treatment of various cardiovascular ailments. For example, Karellas et al introduced heterobivalent molecules targeting β2-adrenergic receptor/adenosine A 1 receptor (β 2 AR/A 1 AR) heteromers in an effort to understand the cross talk among these two cellular cAMP regulating receptors; it was proposed that careful balance between the signaling pathways generated by the two receptor monomers conforming this heteromer could aid in the prevention of certain cardiac arrhythmias . Due to the importance of functions regulated by this receptor system, it has become the focus of significant analysis via heterobivalent ligands …”
Section: Bivalent Molecules For Other Gpcrs To Study Homomers and Het...mentioning
confidence: 99%
“…47 Due to the importance of functions regulated by this receptor system, it has become the focus of significant analysis via heterobivalent ligands. 49 The study of dopamine receptor heteromers with the use of heterobivalent ligands is equally promising. Adenosine A 2A receptor (A 2A R) and dopamine D 2 receptor heteromers (D 2 R/ A 2A R) are of particular interest due to their purported role in Parkinson's disease.…”
Section: ■ Introduction: Bivalent Ligandsmentioning
confidence: 99%
“…Many studies have reported spacers between 15 and 25 atoms such as ligands targeting dimers of the δ- and μ-opioid ( Fig. 1 , molecule 1 ) ( Daniels et al , 2005 ), serotonin ( 2 ) ( Soulier et al , 2005 ), dopamine ( 3 and 4 ) ( Kuhhorn et al , 2011 ; McRobb et al , 2012 ), cannabinoid and μ opioid/cannabinoid ( 5 and 6 ) ( Le Naour et al , 2013 ; Zhang et al , 2010 ), A 2A -D 2 ( 8 ) ( Soriano et al , 2009 ) and A 1 -β 2 ( 9 ) ( Barlow et al , 2013 ) (homo/hetero)dimers to name just a few. Recently, highly active ligands with spacers as large as 44 and 66 atoms ( 7 ) ( Hubner et al , 2016 ) were reported.…”
Section: Introductionmentioning
confidence: 99%
“…The bivalency approach led to ligands with increased affinity or better selectivity toward receptor subtypes. Bivalent ligands have been developed for many GPCRs, such as opioid , adrenergic , dopamine , serotonin , and muscarinic receptor subtypes. In some cases, bivalent ligands were confirmed to bind to dimeric receptors, such as dopamine receptor dimers .…”
Section: Bivalent Ligandsmentioning
confidence: 99%